ANALYSIS OF FACTORS THAT INFLUENCE LABOR ABSORPTION IN WEST JAVA 2011 – 2022 - Nugraha, Nurul Hidayat; Az Zakiyyah, Nurul Azizah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
The title of article is Analysis Of Factors That Influence Labor Absorption In West Java 2011 – 2022 The aim of this research is to analyze the influence of the Regency Minimum Wage (UMK), Gross Regional Domestic Product (GRDP), education level and population on labor absorption in West Java. This research data analysis method uses the Ordinary Least Square (OLS) approach using the Fixed Effect Model. The type of data used is panel data consisting of a combination of cross-section and time series representing districts/cities in West Java for the period 2011 - 2022. The research results show that the influence shown by UMK is negative but not significant, but the influence of GRDP, education level and population show a significantly positive influence on labor absorption in West Java.